EID3 Promotes Cancer Stem Cell-Like Phenotypes in Osteosarcoma through the Activation of PI3K-AKT Signaling Pathway. (28th August 2022) - Wang, Yan; Luo, Shiyong; Wang, Yuxuan; Yang, Shengbang; Huang, Zhitong; Zhu, Xuejin; Cai, Shanghua; Guo, Qifeng; Zhong, Weide; Liu, Sihong
Abstract : The aim of this study is to elucidate molecular mechanism by which E1A-like inhibitor of differentiation 3 (EID3) promotes cancer stem cell-like phenotypes in osteosarcoma. Overexpression of EID3 in osteosarcoma cells generated more spherical clones, enhanced the expression of stemness-associated genes, and promoted chemoresistance, invasion, and metastasis. Furthermore, osteosarcoma cells overexpressing EID3 had increased ability to grow in suspension as osteospheres with high expression of Sox2 and stem cell marker CD133. In addition, knockdown of EID3 reduced sphere formation and inhibited osteosarcoma cell migration and invasion. RNA sequencing and bioinformatics analysis revealed that PI3K-Akt signaling pathway and MAPK pathwayrelated genes were enriched in osteosarcoma cells with high expression of EID3. Taken together, EID3 promotes osteosarcoma, and EID3–PI3K-Akt axis is a potential therapeutic target for osteosarcoma treatment.